Application of the system theory framework to the career development of Korean university students - Lim, Eun Mi; Kang, Hye Jeong; Kim, Tae Sun (International Journal for Educational and Vocational Guidance, 2024)
This study investigates the applicability of the system theory framework (STF) to Korean university students with regard to their career development and counseling. The STF-based career group program content consists of MSCI (My System of Career Influences) and MCC (My Career Chapter), and is conducted over ten sessions for two groups of college students in Korea. Following the program’s conclusion, the participants were asked about its usefulness and their experiences participating. An analysis of the survey results revealed the participants to have rated the program as useful. Subsequently, a qualitative analysis was conducted using the Consensual Qualitative Research (CQR) technique, and four domains and ten categories were derived. Further, the significance and the limitations of the research were discussed.
Keywords: Korean university students; My System of Career Influences(MSCI); Systems Theory Framework(STF)